Preparation method of manganese-zinc wave-absorbing ferrite material and corresponding material
By optimizing the formulation and preparation process of manganese zinc wave absorbing ferrite materials, the problem of insufficient wave absorbing performance of existing ferrite wave absorbing materials is solved, and more efficient electromagnetic wave absorption performance and better material performance are achieved.
Patent Information
- Application Number
- CN202510123318.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-26
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2045-01-26
AI Technical Summary
The existing ferrite wave absorbing materials have insufficient wave absorption performance, which is difficult to meet the industry's strict requirements for efficient electromagnetic wave absorption.
The initial powder is prepared by gel curing method, pre-calcining, strengthening granulation and press sintering process, and optimize the formulation and preparation process of manganese-zeb wave-absorbing ferrite materials to improve their wave-absorbing performance.
The electromagnetic wave absorption performance of manganese zinc wave absorbing ferrite material is significantly optimized, its magnetic resonance and dielectric characteristics in a specific frequency range are improved, the thermal conductivity and high-temperature performance are enhanced, and the magnetic performance and low-temperature densification capabilities are improved.
Smart Images

Figure CN119751038A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of wave absorbing materials, and in particular to a method for preparing a manganese-zinc wave absorbing ferrite material and corresponding materials. Background Art
[0002] Electromagnetic radiation pollution is like an "invisible killer" hidden in modern life, and has been ranked first in the list of key pollution sources that affect the quality of human life and physical and mental health. As a key link in the field of cutting-edge science and technology, absorbing materials are the core technical force to protect people's health and build a solid information security line of defense.
[0003] Ferrite, as a type of metal composite oxide, combines iron and at least one other metal element, has its own ferromagnetic properties and is the "old man" in the field of magnetic absorbing materials. It was invented early and has a very wide range of research. As a dual-complex dielectric material, ferrite has a high magnetic permeability and certain dielectric properties, which has led to its extensive research in the field of absorbing materials. However, how to improve its absorbing performance has always been the direction of continuous exploration and efforts of industry engineers and technicians.
[0004] The Chinese patent with publication number CN114014645A discloses a nickel-zinc ferrite absorber for microwave darkroom and its preparation method. The patent uses the dispersed distribution of TiO2 and ZrO2 in the nickel-zinc ferrite absorber to play a pinning role and improve the absorbing performance. However, since the solution does not involve overall improvement of the process and formula, the performance improvement is limited. With the increasingly stringent technical requirements of the application end, the absorbing performance of the absorber involved in the patent is currently difficult to meet the needs of the industry.
[0005] Therefore, how to optimize the microwave absorption performance of ferrite materials by improving the formula and preparation process of ferrite materials has become a technical problem that needs to be solved urgently. Summary of the invention
[0006] In view of this, in order to overcome the deficiencies of the prior art, the present application aims to provide a method for preparing a manganese-zinc absorbing ferrite material and corresponding materials.
[0007] According to the first aspect of the present application, a method for preparing a manganese-zinc absorbing ferrite material is provided, the method comprising: preparing an initial powder by a gel solidification method, preparing a pre-burned powder by pre-calcining the initial powder, and preparing the manganese-zinc absorbing ferrite material by intensive granulation and then pressing and sintering the pre-burned powder.
[0008] Optionally, in the method for preparing the manganese-zinc absorbing ferrite material of the present application, the initial powder is prepared by reacting a basic powder, ammonium polyacrylate and distilled water, wherein the basic powder includes iron phosphate, iron nitrate, zinc nitrate and manganese nitrate.
[0009] Optionally, in the preparation method of the manganese zinc absorbing ferrite material of the present application, the molar ratio of iron phosphate, iron nitrate, zinc nitrate and manganese nitrate is 2:2:1:1, the mass of ammonium polyacrylate is 0.1-0.2% of the mass of the basic powder, and the mass of distilled water is equal to the mass of the basic powder.
[0010] Optionally, the method for preparing the manganese-zinc absorbing ferrite material of the present application comprises: The base powder, ammonium polyacrylate and distilled water are mixed evenly, the pH value of the obtained mixed solution is adjusted to 8.0-9.5, the mixture is heated to 70-90°C and kept warm for 2-2.5 hours, the obtained gel is heated to 300°C and kept warm for 2 hours to obtain the initial powder; The initial powder is pre-calcined at 980°C for 1.0-1.5h to obtain a pre-calcined powder; The calcined powder and the reinforced powder are ball-milled into a slurry, and the granules are obtained by granulating the slurry; The granules are pressed into shape and gradient sintered to obtain the manganese-zinc absorbing ferrite material.
[0011] Optionally, in the preparation method of the manganese-zinc absorbing ferrite material of the present application, the strengthening powder includes spherical carbonyl nickel, titanium diboride, dysprosium nitrate and cadmium acetate, wherein the mass of the spherical carbonyl nickel is 0.8-1.5% of the mass of the basic powder, the mass of titanium diboride is 0.04-0.1% of the mass of the basic powder, the mass of dysprosium nitrate is 0.4-0.9% of the mass of the basic powder, and the mass of cadmium acetate is 0.1-0.3% of the mass of the basic powder.
[0012] Optionally, in the preparation method of the manganese-zinc absorbing ferrite material of the present application, lubricating powder and ball milling solvent are added during the ball milling of the pre-calcined powder and the strengthened powder. The lubricating powder includes diisooctyl phosphate and molybdenum disulfide. The mass of diisooctyl phosphate is 0.2-0.3% of the mass of the basic powder, and the mass of molybdenum disulfide is 0.1-0.2% of the mass of the basic powder. The ball milling solvent is distilled water of the same mass as the basic powder.
[0013] Optionally, in the preparation method of the manganese-zinc absorbing ferrite material of the present application, when ball-milling the pre-calcined powder and the reinforced powder, spherical carbonyl nickel and the ball-milling solvent are first added, and an abrasive 5 times the mass of the basic powder is used for ball-milling at a speed of 500 r / min for 30 minutes, and lubricating powder and the remaining reinforcing powder are added, and ball-milling is carried out at a speed of 500 r / min for 90-120 minutes.
[0014] Optionally, in the preparation method of the manganese-zinc absorbing ferrite material of the present application, granules are obtained by granulating the slurry, including: adding a 10% by mass fraction polyvinyl alcohol solution to the slurry obtained by ball milling to prepare a spray solution, and spray granulation is performed using the spray solution, and the mass of the polyvinyl alcohol solution is 8-10% of the mass of the basic powder.
[0015] Optionally, in the method for preparing the manganese-zinc absorbing ferrite material of the present application, the granules are pressed and molded and gradient sintered to obtain the manganese-zinc absorbing ferrite material, comprising: The granules are pressed under warm pressure at a pressure of 1.5-2.0 t / cm 2 , the pressing temperature is 120-150°C, the pressing time is 3-5s, and the pressing is naturally cooled to obtain a pressed blank; The pressed billet was heated to 200°C and kept for 2 hours, heated to 300°C and kept for 1 hour, heated to 400°C and kept for 1 hour, heated to 500°C and kept for 1 hour, heated to 900°C and kept for 8 hours, heated to 1200°C and kept for 4 hours, wherein the heating rate is 5°C / min, and cooled to room temperature to obtain manganese zinc absorbing ferrite material.
[0016] According to a second aspect of the present application, a manganese-zinc absorbing ferrite material is provided. The manganese-zinc absorbing ferrite material is prepared according to the above method.
[0017] The preparation method of the manganese-zinc absorbing ferrite material and the corresponding material of the present application have the following beneficial technical effects: The preparation method of the manganese-zinc absorbing ferrite material and the corresponding material of the embodiment of the present application have the following beneficial technical effects through component ratio design and process optimization: 1. Optimize electromagnetic wave absorption performance: Select iron phosphate as the raw material, and adjust the complex dielectric constant and complex magnetic permeability of the material by doping with phosphorus, so that it has higher magnetic resonance and dielectric properties within a specific frequency range, thereby more effectively absorbing electromagnetic waves and converting them into heat energy, reducing electromagnetic wave reflection and interference.
[0018] 2. Improve the microwave absorption performance and microstructure: Spherical carbonyl nickel is used for doping. The introduction of nickel increases the lattice constant, porosity and resistivity, reduces the average grain size and packing density, and increases the hysteresis loss, thus significantly changing the microwave absorption performance. Spherical carbonyl nickel forms a flaky structure after ball milling, which increases the surface activity and surface area, further improving the doping effect.
[0019] 3. Enhanced electrical and thermal conductivity and high temperature performance: The introduction of titanium diboride, whose two-dimensional network structure gives excellent electrical and thermal conductivity, and has a high melting point. During the ferrite sintering process, titanium diboride can form a nucleation precursor, promote uniform grain growth, and stabilize performance. At the same time, its positive resistance temperature coefficient effect can regulate the dielectric constant of high-temperature absorbing materials and improve the absorbing performance under high temperature conditions.
[0020] 4. Improve magnetic properties and low-temperature densification: Use dysprosium nitrate. The addition of dysprosium increases the bond length and radius of the tetrahedral and octahedral sites in the ferrite, increases the saturation magnetization and coercivity, and thus enhances the wave absorption characteristics. At the same time, the low melting point of cadmium acetate forms grain boundaries during the liquid phase sintering process, promotes the transfer of matter and energy, achieves low-temperature densification, reduces sintering problems, and improves wave absorption performance.
[0021] 5. Improve lubrication and wave absorption performance: Diisooctyl phosphate and molybdenum disulfide are used as lubricants. Diisooctyl phosphate forms a liquid lubricating film during the pressing process, and molybdenum disulfide exhibits excellent electronic properties due to its high specific surface area and polymorphism. The quantum confinement effect can change its band gap, thereby improving the wave absorption performance while lubricating. In addition, the molybdenum element forms a crystal nucleus during the sintering process, which promotes the homogenization of the grains, reduces the sintering temperature and improves the wave absorption performance.
[0022] 6. Improve slurry stability and rheology: Use ammonium polyacrylate as a dispersant. Its ionic polymer properties give it good water absorption, adhesion and dispersibility, which can improve the stability and rheology of ferrite slurry and optimize the ball milling process.
[0023] 7. Improve the density of the embryo and sintering stability: The warm pressing molding process is used to significantly improve the density of the ferrite embryo, effectively preventing problems such as breakage caused by excessive sintering shrinkage during the sintering process.
[0024] 8. Optimize sintering process and yield rate: adopt gradient temperature rise sintering process, keep warm at 200℃, 300℃, 400℃, 500℃, fully remove moisture, and prevent Fe 2+ Oxidation can also be prevented by the evaporation of water and binder too quickly, which can prevent the blank from deforming or cracking, thus significantly improving the sintering yield and material performance stability. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0026] Figure 1 This is a scanning electron microscope image of the manganese-zinc absorbing ferrite material prepared in Example 1 of the present application; Figure 2 This is a scanning electron microscope image of the manganese-zinc absorbing ferrite material prepared in Example 2 of the present application; Figure 3 This is a scanning electron microscope image of the manganese-zinc absorbing ferrite material prepared in Example 3 of the present application; Figure 4 This is a scanning electron microscope image of the manganese-zinc absorbing ferrite material prepared in Example 4 of the present application; Figure 5 This is a scanning electron microscope image of the manganese-zinc absorbing ferrite material prepared in Example 5 of the present application; Figure 6 This is a scanning electron microscope image of the manganese-zinc absorbing ferrite material prepared in Example 6 of the present application; Figure 7 This is the XRD spectrum of the manganese zinc absorbing ferrite material prepared in Examples 1-6 of the present application. DETAILED DESCRIPTION
[0027] The embodiments of the present application are described in detail below with reference to the accompanying drawings.
[0028] It should be noted that the following embodiments and features in the embodiments may be combined with each other in the absence of conflict; and, based on the embodiments in the present disclosure, all other embodiments obtained by ordinary technicians in the field without making any creative work are within the scope of protection of the present disclosure.
[0029] It should be noted that various aspects of the embodiments within the scope of the appended claims are described below. It should be apparent that the aspects described herein may be embodied in a wide variety of forms, and any specific structure and / or function described herein is merely illustrative. Based on the present disclosure, it should be understood by those skilled in the art that an aspect described herein may be implemented independently of any other aspect, and two or more of these aspects may be combined in various ways. For example, any number of aspects described herein may be used to implement the device and / or practice the method. In addition, other structures and / or functionalities other than one or more of the aspects described herein may be used to implement this device and / or practice this method.
[0030] Example 1 Mixing a basic powder, ammonium polyacrylate and distilled water uniformly, wherein the basic powder includes iron phosphate, iron nitrate, zinc nitrate and manganese nitrate, the molar ratio of iron phosphate, iron nitrate, zinc nitrate and manganese nitrate is 2:2:1:1, the mass of ammonium polyacrylate is 0.2% of the mass of the basic powder, and the mass of distilled water is equal to the mass of the basic powder; adjusting the pH value of the obtained mixed solution to 8.0, heating to 90°C and keeping the temperature for 2.0h, heating the obtained gel to 300°C and keeping the temperature for 2h to obtain an initial powder; The initial powder was pre-calcined at 980°C for 1.0h to obtain a pre-calcined powder; The pre-calcined powder and the strengthening powder are ball-milled into a slurry, wherein the strengthening powder includes spherical carbonyl nickel, titanium diboride, dysprosium nitrate and cadmium acetate, wherein the mass of the spherical carbonyl nickel is 1.4% of the mass of the basic powder, the mass of titanium diboride is 0.09% of the mass of the basic powder, the mass of dysprosium nitrate is 0.9% of the mass of the basic powder, and the mass of cadmium acetate is 0.3% of the mass of the basic powder; when the pre-calcined powder and the strengthening powder are ball-milled, the spherical carbonyl nickel and the ball-milling solvent are first added, and the abrasive 5 times the mass of the basic powder is used for ball-milling at a speed of 500r / min for 30min, and the lubricating powder and the remaining strengthening powder are added, and the ball-milling is carried out at a speed of 500r / min for 90min. The lubricating powder includes diisooctyl phosphate and molybdenum disulfide, the mass of diisooctyl phosphate is 0.3% of the mass of the basic powder, the mass of molybdenum disulfide is 0.2% of the mass of the basic powder, and the ball-milling solvent is distilled water of the same mass as the basic powder.
[0031] The slurry obtained by ball milling is added to a polyvinyl alcohol solution with a mass fraction of 10% to prepare a spray solution, and the spray solution is used for spray granulation, wherein the mass of the polyvinyl alcohol solution is 8% of the mass of the basic powder, to obtain granules; The granules are pressed and sintered by gradient. Specifically, the granules are pressed by warm pressure at a pressure of 1.0 t / cm 2 , the pressing temperature is 120℃, the pressing time is 3s, and it is naturally cooled to obtain a pressed blank; the pressed blank is heated to 200℃ and kept warm for 2h, heated to 300℃ and kept warm for 1h, heated to 400℃ and kept warm for 1h, heated to 500℃ and kept warm for 1h, heated to 900℃ and kept warm for 8h, heated to 1200℃ and kept warm for 4h, wherein the heating rate is 5℃ / min, and cooled to room temperature to obtain a manganese-zinc absorbing ferrite material.
[0032] Example 2 Mixing a basic powder, ammonium polyacrylate and distilled water uniformly, wherein the basic powder includes iron phosphate, iron nitrate, zinc nitrate and manganese nitrate, the molar ratio of iron phosphate, iron nitrate, zinc nitrate and manganese nitrate is 2:2:1:1, the mass of ammonium polyacrylate is 0.1% of the mass of the basic powder, and the mass of distilled water is equal to the mass of the basic powder; adjusting the pH value of the obtained mixed solution to 9.5, heating to 70°C and keeping the temperature for 2.5 hours, heating the obtained gel to 300°C and keeping the temperature for 2 hours, and obtaining an initial powder; The initial powder was pre-calcined at 980°C for 1.5 hours to obtain a pre-calcined powder; The pre-calcined powder and the strengthening powder are ball-milled into a slurry, wherein the strengthening powder includes spherical carbonyl nickel, titanium diboride, dysprosium nitrate and cadmium acetate, wherein the mass of the spherical carbonyl nickel is 0.8% of the mass of the basic powder, the mass of titanium diboride is 0.04% of the mass of the basic powder, the mass of dysprosium nitrate is 0.4% of the mass of the basic powder, and the mass of cadmium acetate is 0.1% of the mass of the basic powder; when the pre-calcined powder and the strengthening powder are ball-milled, the spherical carbonyl nickel and the ball-milling solvent are first added, and the abrasive 5 times the mass of the basic powder is used for ball-milling at a speed of 500r / min for 30min, and the lubricating powder and the remaining strengthening powder are added, and the ball-milling is carried out at a speed of 500r / min for 120min. The lubricating powder includes diisooctyl phosphate and molybdenum disulfide, the mass of diisooctyl phosphate is 0.2% of the mass of the basic powder, the mass of molybdenum disulfide is 0.1% of the mass of the basic powder, and the ball-milling solvent is distilled water of the same mass as the basic powder.
[0033] The slurry obtained by ball milling is added to a polyvinyl alcohol solution with a mass fraction of 10% to prepare a spray solution, and the spray solution is used for spray granulation, wherein the mass of the polyvinyl alcohol solution is 10% of the mass of the basic powder to obtain granules; The granules are pressed and sintered by gradient. Specifically, the granules are pressed by warm pressure at a pressure of 1.5 t / cm 2 , the pressing temperature is 150℃, the pressing time is 3.5s, and it is naturally cooled to obtain a pressed blank; the pressed blank is heated to 200℃ and kept warm for 2h, heated to 300℃ and kept warm for 1h, heated to 400℃ and kept warm for 1h, heated to 500℃ and kept warm for 1h, heated to 900℃ and kept warm for 8h, heated to 1200℃ and kept warm for 4h, wherein the heating rate is 5℃ / min, cooled to room temperature, and a manganese-zinc absorbing ferrite material is obtained.
[0034] Example 3 Mixing a basic powder, ammonium polyacrylate and distilled water uniformly, wherein the basic powder includes iron phosphate, iron nitrate, zinc nitrate and manganese nitrate, the molar ratio of iron phosphate, iron nitrate, zinc nitrate and manganese nitrate is 2:2:1:1, the mass of ammonium polyacrylate is 0.12% of the mass of the basic powder, and the mass of distilled water is equal to the mass of the basic powder; adjusting the pH value of the obtained mixed solution to 8.2, heating to 80°C and keeping the temperature for 2.0h, heating the obtained gel to 300°C and keeping the temperature for 2h to obtain an initial powder; The initial powder was pre-calcined at 980°C for 1.1h to obtain a pre-calcined powder; The pre-calcined powder and the strengthening powder are ball-milled into a slurry, wherein the strengthening powder includes spherical carbonyl nickel, titanium diboride, dysprosium nitrate and cadmium acetate, wherein the mass of the spherical carbonyl nickel is 1.0% of the mass of the basic powder, the mass of titanium diboride is 0.05% of the mass of the basic powder, the mass of dysprosium nitrate is 0.8% of the mass of the basic powder, and the mass of cadmium acetate is 0.26% of the mass of the basic powder; when the pre-calcined powder and the strengthening powder are ball-milled, the spherical carbonyl nickel and the ball-milling solvent are first added, and the abrasive 5 times the mass of the basic powder is used for ball-milling at a speed of 500r / min for 30min, and the lubricating powder and the remaining strengthening powder are added, and the ball-milling is carried out at a speed of 500r / min for 110min. The lubricating powder includes diisooctyl phosphate and molybdenum disulfide, the mass of diisooctyl phosphate is 0.28% of the mass of the basic powder, the mass of molybdenum disulfide is 0.18% of the mass of the basic powder, and the ball-milling solvent is distilled water of the same mass as the basic powder.
[0035] The slurry obtained by ball milling is added with a 10% by mass polyvinyl alcohol solution to prepare a spray solution, and the spray solution is used for spray granulation, wherein the mass of the polyvinyl alcohol solution is 8.5% of the mass of the basic powder to obtain granules; The granules are pressed and gradient sintered. Specifically, the granules are pressed at a temperature of 1.9 t / cm 2 , the pressing temperature is 130℃, the pressing time is 4.0s, and it is naturally cooled to obtain a pressed blank; the pressed blank is heated to 200℃ and kept warm for 2h, heated to 300℃ and kept warm for 1h, heated to 400℃ and kept warm for 1h, heated to 500℃ and kept warm for 1h, heated to 900℃ and kept warm for 8h, heated to 1200℃ and kept warm for 4h, wherein the heating rate is 5℃ / min, and cooled to room temperature to obtain a manganese-zinc absorbing ferrite material.
[0036] Example 4 Mixing a basic powder, ammonium polyacrylate and distilled water uniformly, wherein the basic powder includes iron phosphate, iron nitrate, zinc nitrate and manganese nitrate, the molar ratio of iron phosphate, iron nitrate, zinc nitrate and manganese nitrate is 2:2:1:1, the mass of ammonium polyacrylate is 0.14% of the mass of the basic powder, and the mass of distilled water is equal to the mass of the basic powder; adjusting the pH value of the obtained mixed solution to 8.6, heating to 85°C and keeping the temperature for 2.5 hours, heating the obtained gel to 300°C and keeping the temperature for 2 hours, and obtaining an initial powder; The initial powder was pre-calcined at 980°C for 1.2 hours to obtain a pre-calcined powder; The pre-calcined powder and the strengthening powder are ball-milled into a slurry, wherein the strengthening powder includes spherical carbonyl nickel, titanium diboride, dysprosium nitrate and cadmium acetate, wherein the mass of the spherical carbonyl nickel is 1.2% of the mass of the basic powder, the mass of titanium diboride is 0.06% of the mass of the basic powder, the mass of dysprosium nitrate is 0.7% of the mass of the basic powder, and the mass of cadmium acetate is 0.22% of the mass of the basic powder; when the pre-calcined powder and the strengthening powder are ball-milled, the spherical carbonyl nickel and the ball-milling solvent are first added, and the abrasive 5 times the mass of the basic powder is used for ball-milling at a speed of 500r / min for 30min, and the lubricating powder and the remaining strengthening powder are added, and the ball-milling is carried out at a speed of 500r / min for 100min. The lubricating powder includes diisooctyl phosphate and molybdenum disulfide, the mass of diisooctyl phosphate is 0.26% of the mass of the basic powder, the mass of molybdenum disulfide is 0.16% of the mass of the basic powder, and the ball-milling solvent is distilled water of the same mass as the basic powder.
[0037] The slurry obtained by ball milling is added with a 10% by mass polyvinyl alcohol solution to prepare a spray solution, and the spray solution is used for spray granulation, wherein the mass of the polyvinyl alcohol solution is 9.8% of the mass of the basic powder, to obtain granules; The granules are pressed and sintered by gradient. Specifically, the granules are pressed by warm pressure at a pressure of 1.8 t / cm 2 , the pressing temperature is 140℃, the pressing time is 5s, and it is naturally cooled to obtain a pressed blank; the pressed blank is heated to 200℃ and kept warm for 2h, heated to 300℃ and kept warm for 1h, heated to 400℃ and kept warm for 1h, heated to 500℃ and kept warm for 1h, heated to 900℃ and kept warm for 8h, heated to 1200℃ and kept warm for 4h, wherein the heating rate is 5℃ / min, and cooled to room temperature to obtain a manganese-zinc absorbing ferrite material.
[0038] Example 5 Mixing a basic powder, ammonium polyacrylate and distilled water uniformly, wherein the basic powder includes iron phosphate, iron nitrate, zinc nitrate and manganese nitrate, the molar ratio of iron phosphate, iron nitrate, zinc nitrate and manganese nitrate is 2:2:1:1, the mass of ammonium polyacrylate is 0.18% of the mass of the basic powder, and the mass of distilled water is equal to the mass of the basic powder; adjusting the pH value of the obtained mixed solution to 9.0, heating to 75°C and keeping the temperature for 2.0h, heating the obtained gel to 300°C and keeping the temperature for 2h to obtain an initial powder; The initial powder was pre-calcined at 980°C for 1.3 hours to obtain a pre-calcined powder; The pre-calcined powder and the strengthening powder are ball-milled into a slurry, wherein the strengthening powder includes spherical carbonyl nickel, titanium diboride, dysprosium nitrate and cadmium acetate, wherein the mass of the spherical carbonyl nickel is 1.2% of the mass of the basic powder, the mass of titanium diboride is 0.08% of the mass of the basic powder, the mass of dysprosium nitrate is 0.6% of the mass of the basic powder, and the mass of cadmium acetate is 0.16% of the mass of the basic powder; when the pre-calcined powder and the strengthening powder are ball-milled, the spherical carbonyl nickel and the ball-milling solvent are first added, and the abrasive 5 times the mass of the basic powder is used for ball-milling at a speed of 500r / min for 30min, and the lubricating powder and the remaining strengthening powder are added, and the ball-milling is carried out at a speed of 500r / min for 115min. The lubricating powder includes diisooctyl phosphate and molybdenum disulfide, the mass of diisooctyl phosphate is 0.24% of the mass of the basic powder, the mass of molybdenum disulfide is 0.14% of the mass of the basic powder, and the ball-milling solvent is distilled water of the same mass as the basic powder.
[0039] The slurry obtained by ball milling was added with a 10% by mass polyvinyl alcohol solution to prepare a spray solution, and the spray solution was used for spray granulation, wherein the mass of the polyvinyl alcohol solution was 9.2% of the mass of the basic powder, to obtain granules; The granules are pressed and sintered by gradient. Specifically, the granules are pressed by warm pressure at a pressure of 1.7 t / cm 2 , the pressing temperature is 145°C, the pressing time is 4.0s, and it is naturally cooled to obtain a pressed blank; the pressed blank is heated to 200°C and kept warm for 2h, heated to 300°C and kept warm for 1h, heated to 400°C and kept warm for 1h, heated to 500°C and kept warm for 1h, heated to 900°C and kept warm for 8h, heated to 1200°C and kept warm for 4h, wherein the heating rate is 5°C / min, cooled to room temperature, and a manganese-zinc absorbing ferrite material is obtained.
[0040] Example 6 Mixing a basic powder, ammonium polyacrylate and distilled water uniformly, wherein the basic powder includes iron phosphate, iron nitrate, zinc nitrate and manganese nitrate, the molar ratio of iron phosphate, iron nitrate, zinc nitrate and manganese nitrate is 2:2:1:1, the mass of ammonium polyacrylate is 0.15% of the mass of the basic powder, and the mass of distilled water is equal to the mass of the basic powder; adjusting the pH value of the obtained mixed solution to 9.2, heating to 80°C and keeping the temperature for 2.0h, heating the obtained gel to 300°C and keeping the temperature for 2h to obtain an initial powder; The initial powder was pre-calcined at 980°C for 1.4 hours to obtain a pre-calcined powder; The pre-calcined powder and the strengthening powder are ball-milled into a slurry, wherein the strengthening powder includes spherical carbonyl nickel, titanium diboride, dysprosium nitrate and cadmium acetate, wherein the mass of the spherical carbonyl nickel is 1.3% of the mass of the basic powder, the mass of titanium diboride is 0.09% of the mass of the basic powder, the mass of dysprosium nitrate is 0.5% of the mass of the basic powder, and the mass of cadmium acetate is 0.14% of the mass of the basic powder; when the pre-calcined powder and the strengthening powder are ball-milled, the spherical carbonyl nickel and the ball-milling solvent are first added, and the abrasive 5 times the mass of the basic powder is used for ball-milling at a speed of 500r / min for 30min, and the lubricating powder and the remaining strengthening powder are added, and the ball-milling is carried out at a speed of 500r / min for 95min. The lubricating powder includes diisooctyl phosphate and molybdenum disulfide, the mass of diisooctyl phosphate is 0.22% of the mass of the basic powder, the mass of molybdenum disulfide is 0.12% of the mass of the basic powder, and the ball-milling solvent is distilled water of the same mass as the basic powder.
[0041] The slurry obtained by ball milling is added to a polyvinyl alcohol solution with a mass fraction of 10% to prepare a spray solution, and the spray solution is used for spray granulation, wherein the mass of the polyvinyl alcohol solution is 9.0% of the mass of the basic powder, to obtain granules; The granules are pressed and sintered by gradient. Specifically, the granules are pressed by warm pressure at a pressure of 1.6 t / cm 2 , the pressing temperature is 125℃, the pressing time is 5s, and it is naturally cooled to obtain a pressed blank; the pressed blank is heated to 200℃ and kept warm for 2h, heated to 300℃ and kept warm for 1h, heated to 400℃ and kept warm for 1h, heated to 500℃ and kept warm for 1h, heated to 900℃ and kept warm for 8h, heated to 1200℃ and kept warm for 4h, wherein the heating rate is 5℃ / min, and cooled to room temperature to obtain a manganese-zinc absorbing ferrite material.
[0042] Example 7 The cross-sections of the manganese-zinc absorbing ferrite materials prepared in Examples 1-6 were observed using a scanning electron microscope (Zeiss GeminiSEM 300, Germany). The acceleration voltage used was 5 kV and the magnification was 2000 times. Figure 1 This is a scanning electron microscope image of the manganese-zinc absorbing ferrite material prepared in Example 1 of the present application. Figure 2 This is a scanning electron microscope image of the manganese-zinc absorbing ferrite material prepared in Example 2 of the present application. Figure 3 This is a scanning electron microscope image of the manganese-zinc absorbing ferrite material prepared in Example 3 of the present application. Figure 4 This is a scanning electron microscope image of the manganese-zinc absorbing ferrite material prepared in Example 4 of the present application. Figure 5 This is a scanning electron microscope image of the manganese-zinc absorbing ferrite material prepared in Example 5 of the present application. Figure 6This is a scanning electron microscope image of the manganese-zinc absorbing ferrite material prepared in Example 6 of the present application.
[0043] like Figures 1 to 6 As shown, the prepared manganese zinc absorbing ferrite material of the embodiment of the present application has a grain size distribution in the range of 3-10μm, and the grain size distribution is uniform, the grain boundary is obvious, and there is no obvious air gap on the grain boundary. This structure is of great significance to the absorbing performance: the appropriate grain size helps to optimize the absorbing performance; the uniform grain distribution indicates that the crystal growth of the material is relatively consistent during the preparation process, which not only has good quality stability, but also is conducive to the consistency of the absorbing performance of the material; and the clear grain boundary reflects that the material has a relatively regular crystal structure, which creates favorable conditions for the orderly distribution and movement of electrons, magnetic domains, etc. inside the material.
[0044] The structure of the manganese-zinc absorbing ferrite material prepared in Examples 1-6 was characterized and analyzed using a DX-2700B X-ray diffractometer produced by Liaoning Dandong Haoyuan, using copper as a target, the voltage value was set to 30 kV, the current value was set to 20 mA, the step size was set to 0.03°, and the scanning range included two ranges: 2θ=10-80° and 2θ=5-80°. The XRD patterns of the manganese-zinc absorbing ferrite material prepared in Examples 1-6 are shown in Figure 7 .
[0045] Figure 7 The XRD patterns of the manganese-zinc absorbing ferrite materials prepared in Examples 1-6 of the present application are as follows: Figure 7 As shown, by comparing with JCPDS Cards#-74-2402, the diffraction peaks of Examples 1-6 correspond one to one with planes (111), (220), (311), (222), (400), (422), (511), (440), (620), and (533), and a characteristic peak of the spinel phase is observed at 2θ near 35°, namely, a high-intensity reflection peak (311), indicating that the manganese-zinc absorbing ferrite materials prepared in Examples 1-6 of the present application are all single-phase cubic spinel structures.
[0046] The coaxial transmission reflection method was adopted and the E5071C type vector network analyzer was used to test the wave absorbing performance of the manganese-zinc absorbing ferrite material prepared in Examples 1-6 of the present application. The test method is the coaxial transmission reflection method. The E5071C type vector network analyzer used in this embodiment can test the wave absorbing performance of the material by scanning the transmission and reflection signals of each working frequency point in the measured frequency band. The test results of the reflection loss of the manganese-zinc absorbing ferrite material prepared in Examples 1-6 of the present application are shown in Table 1.
[0047] Table 1
[0048] Table 1 shows the reflection loss RL values of the manganese-zinc absorbing ferrite materials prepared in Examples 1 to 6. As shown in Table 1, at the test frequency f=100MHz, the reflection losses of the manganese-zinc absorbing ferrite materials prepared in all Examples are more than -35dB, and at the test frequency f=400MHz, the reflection losses of the manganese-zinc absorbing ferrite materials prepared in all Examples are more than -20dB, indicating that the manganese-zinc absorbing ferrite materials prepared in the examples of the present application have good absorbing performance.
[0049] The preparation method of the manganese-zinc absorbing ferrite material and the corresponding material of the embodiment of the present application have the following beneficial technical effects through component ratio design and process optimization: 1. Optimize electromagnetic wave absorption performance: Select iron phosphate as the raw material, and adjust the complex dielectric constant and complex magnetic permeability of the material by doping with phosphorus, so that it has higher magnetic resonance and dielectric properties within a specific frequency range, thereby more effectively absorbing electromagnetic waves and converting them into heat energy, reducing electromagnetic wave reflection and interference.
[0050] 2. Improve the microwave absorption performance and microstructure: Spherical carbonyl nickel is used for doping. The introduction of nickel increases the lattice constant, porosity and resistivity, reduces the average grain size and packing density, and increases the hysteresis loss, thus significantly changing the microwave absorption performance. Spherical carbonyl nickel forms a flaky structure after ball milling, which increases the surface activity and surface area, further improving the doping effect.
[0051] 3. Enhanced electrical and thermal conductivity and high temperature performance: The introduction of titanium diboride, whose two-dimensional network structure gives excellent electrical and thermal conductivity, and has a high melting point. During the ferrite sintering process, titanium diboride can form a nucleation precursor, promote uniform grain growth, and stabilize performance. At the same time, its positive resistance temperature coefficient effect can regulate the dielectric constant of high-temperature absorbing materials and improve the absorbing performance under high temperature conditions.
[0052] 4. Improve magnetic properties and low-temperature densification: Use dysprosium nitrate. The addition of dysprosium increases the bond length and radius of the tetrahedral and octahedral sites in the ferrite, increases the saturation magnetization and coercivity, and thus enhances the wave absorption characteristics. At the same time, the low melting point of cadmium acetate forms grain boundaries during the liquid phase sintering process, promotes the transfer of matter and energy, achieves low-temperature densification, reduces sintering problems, and improves wave absorption performance.
[0053] 5. Improve lubrication and wave absorption performance: Diisooctyl phosphate and molybdenum disulfide are used as lubricants. Diisooctyl phosphate forms a liquid lubricating film during the pressing process, and molybdenum disulfide exhibits excellent electronic properties due to its high specific surface area and polymorphism. The quantum confinement effect can change its band gap, thereby improving the wave absorption performance while lubricating. In addition, the molybdenum element forms a crystal nucleus during the sintering process, which promotes the homogenization of the grains, reduces the sintering temperature and improves the wave absorption performance.
[0054] 6. Improve slurry stability and rheology: Use ammonium polyacrylate as a dispersant. Its ionic polymer properties give it good water absorption, adhesion and dispersibility, which can improve the stability and rheology of ferrite slurry and optimize the ball milling process.
[0055] 7. Improve the density of the embryo and sintering stability: The warm pressing molding process is used to significantly improve the density of the ferrite embryo, effectively preventing problems such as breakage caused by excessive sintering shrinkage during the sintering process.
[0056] 8. Optimize sintering process and yield rate: adopt gradient temperature rise sintering process, keep warm at 200℃, 300℃, 400℃, 500℃, fully remove moisture, and prevent Fe 2+ Oxidation can also be prevented by the evaporation of water and binder too quickly, which can prevent the blank from deforming or cracking, thus significantly improving the sintering yield and material performance stability.
[0057] The above is only a specific implementation of the present application, but the protection scope of the present application is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed in the present application should be included in the protection scope of the present application. Therefore, the protection scope of the present application shall be based on the protection scope of the claims.
Claims
1. A method for preparing a manganese-zinc absorbing ferrite material, characterized in that: The method comprises: preparing an initial powder by a gel solidification method, preparing a pre-burned powder by pre-calcining the initial powder, and preparing a manganese-zinc absorbing ferrite material by pressing and sintering the pre-burned powder after strengthening granulation.
2. The method for preparing the manganese-zinc absorbing ferrite material according to claim 1, characterized in that: The initial powder is prepared by reacting a basic powder, ammonium polyacrylate and distilled water, wherein the basic powder includes iron phosphate, iron nitrate, zinc nitrate and manganese nitrate.
3. The method for preparing the manganese-zinc absorbing ferrite material according to claim 2, characterized in that: The molar ratio of ferric phosphate, ferric nitrate, zinc nitrate and manganese nitrate is 2:2:1:1, the mass of ammonium polyacrylate is 0.1-0.2% of the mass of the basic powder, and the mass of distilled water is equal to the mass of the basic powder.
4. The method for preparing the manganese-zinc absorbing ferrite material according to claim 1, characterized in that: The method comprises: The base powder, ammonium polyacrylate and distilled water are mixed evenly, the pH value of the obtained mixed solution is adjusted to 8.0-9.5, the mixture is heated to 70-90°C and kept warm for 2-2.5 hours, the obtained gel is heated to 300°C and kept warm for 2 hours to obtain the initial powder; The initial powder is pre-calcined at 980°C for 1.0-1.5h to obtain a pre-calcined powder; The calcined powder and the reinforced powder are ball-milled into a slurry, and the granules are obtained by granulating the slurry; The granules are pressed into shape and gradient sintered to obtain the manganese-zinc absorbing ferrite material.
5. The method for preparing the manganese-zinc absorbing ferrite material according to claim 4, characterized in that: The strengthening powder includes spherical nickel carbonyl, titanium diboride, dysprosium nitrate and cadmium acetate, wherein the mass of spherical nickel carbonyl is 0.8-1.5% of the mass of the basic powder, the mass of titanium diboride is 0.04-0.1% of the mass of the basic powder, the mass of dysprosium nitrate is 0.4-0.9% of the mass of the basic powder, and the mass of cadmium acetate is 0.1-0.3% of the mass of the basic powder.
6. The method for preparing the manganese-zinc absorbing ferrite material according to claim 4, characterized in that: When the pre-calcined powder and the strengthened powder are ball-milled, lubricating powder and ball-milling solvent are added. The lubricating powder includes diisooctyl phosphate and molybdenum disulfide. The mass of diisooctyl phosphate is 0.2-0.3% of the mass of the basic powder, and the mass of molybdenum disulfide is 0.1-0.2% of the mass of the basic powder. The ball-milling solvent is distilled water of the same mass as the basic powder.
7. The method for preparing the manganese-zinc absorbing ferrite material according to claim 6, characterized in that: When the pre-calcined powder and the reinforcing powder are ball-milled, spherical carbonyl nickel and the ball-milling solvent are first added, and the abrasive 5 times the mass of the basic powder is used for ball-milling at a speed of 500 r / min for 30 minutes. The lubricating powder and the remaining reinforcing powder are added, and the ball-milling is carried out at a speed of 500 r / min for 90-120 minutes.
8. The method for preparing the manganese-zinc absorbing ferrite material according to claim 4, characterized in that: The granules are obtained by granulating the slurry, including: adding a 10% by mass polyvinyl alcohol solution to the slurry obtained by ball milling to obtain a spray solution, and using the spray solution for spray granulation, wherein the mass of the polyvinyl alcohol solution is 8-10% of the mass of the basic powder.
9. The method for preparing the manganese-zinc absorbing ferrite material according to claim 4, characterized in that: The granules are pressed and sintered by gradient to obtain the manganese-zinc absorbing ferrite material, including: The granules are pressed under warm pressure at a pressure of 1.5-2.0 t / cm 2 , the pressing temperature is 120-150°C, the pressing time is 3-5s, and the pressing is naturally cooled to obtain a pressed blank; The pressed billet was heated to 200°C and kept for 2 hours, heated to 300°C and kept for 1 hour, heated to 400°C and kept for 1 hour, heated to 500°C and kept for 1 hour, heated to 900°C and kept for 8 hours, heated to 1200°C and kept for 4 hours, wherein the heating rate is 5°C / min, and cooled to room temperature to obtain manganese zinc absorbing ferrite material.
10. A manganese-zinc absorbing ferrite material, characterized in that: The manganese zinc absorbing ferrite material is prepared according to any one of the methods described in claims 1-9.
Citation Information
Patent Citations
Nickel-zinc ferrite wave absorbing plate for microwave anechoic chamber and preparation method thereof
CN114014645A
Method for quick sintering of micro-crystal ferrite magnetic core part
CN101266859A
Method for directly preparing MnZn ferrite material from nanocrystalline MnZn powder
CN101481243A
Method for preparing manganese-zinc ferrite wave absorbing material from casting waste dust
CN108863334A
Preparation method of carbon compounded manganese-zinc ferrite broadband wave-absorbing material
CN110526702A